2008
DOI: 10.1590/s0004-27302008000900009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes e doenças auto-imunes: prevalência de doença celíaca em crianças e adolescentes portadores de diabetes melito tipo 1

Abstract: OBJETIVO: Determinar a prevalência de doença celíaca em crianças e adolescentes portadores de diabetes melito tipo1 (DM1) no Instituto Estadual de Diabetes e Endocrinologia Luiz Capriglione (IEDE). MÉTODOS: Foram analisadas amostras de sangue de 120 crianças e adolescentes portadores de DM1 do Ambulatório de Diabetes do IEDE para a pesquisa do anticorpo antitransglutaminase tecidual humana IgA e dosagem da IgA sérica. Aqueles com sorologia positiva foram encaminhados para endoscopia digestiva alta com biópsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 12 publications
1
2
1
7
Order By: Relevance
“…Comparing our data with the few screening studies carried out in Europe and in non-European Union countries, no significant differences are noted, but the difficulty and cost of arriving at a diagnosis highlights the social and economic problem,23,24 especially in Africa and Southwest Asia where, during episodes of infectious illness and epidemic diarrhea, humanitarian associations distribute grain and powdered milk, causing re-emergence of symptomatic celiac disease 25,26. Last, but not least, nostalgia is an emerging problem affecting sick immigrant children in Europe.…”
Section: Discussioncontrasting
confidence: 42%
“…Comparing our data with the few screening studies carried out in Europe and in non-European Union countries, no significant differences are noted, but the difficulty and cost of arriving at a diagnosis highlights the social and economic problem,23,24 especially in Africa and Southwest Asia where, during episodes of infectious illness and epidemic diarrhea, humanitarian associations distribute grain and powdered milk, causing re-emergence of symptomatic celiac disease 25,26. Last, but not least, nostalgia is an emerging problem affecting sick immigrant children in Europe.…”
Section: Discussioncontrasting
confidence: 42%
“…In Brazilian children with T1DMA, the prevalence of anti-tTG ranged from 2.5% to 15.8%. [ 32 35 36 37 ] A recent Brazilian study reported a prevalence of 3.1% of CD in patients diagnosed with T1DM. [ 5 ] Consistent with these studies, the prevalence of anti-tTG IgA human antibodies in our study was 7%.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência da DC entre os pacientes diabéticos varia de 2,2% a 13,8% (3,4), média de 4,1% nos países europeus, consideravelmente superior à prevalência da DC na população geral (0,5%-1%) (5). No Brasil existem poucos estudos e a investigação da DC em pacientes diabéticos ainda não é rotina em muitos serviços.…”
Section: Prevalência Da Doença Celíaca No Dm1unclassified